CD89/CD35 Expression Ratio in Salivary Neutrophil as an Early Detection Marker for Severe Early Childhood Caries - Luthfi, Muhammad; Oki, Aqsa Sjuhada; Indrawati, Retno; Rifai, Muhaimin; Dachlan, Yoes Prijatna; Razak, Fathilah Abdul (European Journal of Dentistry, 2020)
Objectives To analyze CD35/CD89 expression ratio on the surface of neutrophils as an early detection marker for S-ECC.Materials and Methods Saliva was collected from 4- to 6-year-old kindergarten students. Salivary neutrophils were obtained by instructing the subjects to rinse their mouth with 1 mL of sterile 1.5% NaCl for 30 seconds before expectorating it into a sterile glass. The expression of CFSE+CD35+ and CFSE+CD89+was measured and analyzed using flow cytometry.Results The expression of CFSE+CD89+ in the caries-free group (2.46 ± 0.39) was significantly lower than that in the S-ECC group (3.41 ± 1.11), with a p-value of 0.0001, while the expression of CFSE+CD35+ in the caries-free group was (2.35 ± 0.56) compared with (1.54 ± 0.35) (p = 0.0001) in the S-ECC group.Conclusions The expression ratio of CFSE+CD89+ and CFSE+CD35+constitutes a marker for S-ECC.
Keywords: CD89; CD35; neutrophils; caries; biomarker